2021
DOI: 10.1002/pssb.202100178
|View full text |Cite
|
Sign up to set email alerts
|

2D V–VI Binary Nanosheets with Square Lattice: A Theoretical Investigation

Abstract: It is of paramount importance to explore novel 2D materials with unique structural and physical properties that are promising for application in a specific field. Herein, eleven monolayers with novel square lattice are studied, including S‐SeN2, S‐TeN2, S‐SP2, S‐SeP2, S‐TeP2, S‐SAs2, S‐SeAs2, S‐TeAs2, S‐SSb2, S‐SeSb2, and S‐TeSb2, via first‐principles calculations. Through stability screening, only the S‐SeN2 monolayer, where each Se atom is tetracoordinated with four N atoms, and each N atom bridges two atoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…54 Qiao et al found that the SeN 2 monolayer is the only stable 2D crystal among 11 V-VI binary nanosheets with a square lattice. 55 Experimentally, by Auassisted mechanical exfoliation, Huang et al prepared more than 40 types of large-area single-crystalline monolayers, among which is GeS 2 in P 4m2 symmetry with a square lattice, but its properties have not been studied so far. 56 The above exciting ndings, especially the successful synthesis of the square conguration of the GeS 2 monolayer, prompt important questions: Would the other 2D TMDs adopt a square structure?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 Qiao et al found that the SeN 2 monolayer is the only stable 2D crystal among 11 V-VI binary nanosheets with a square lattice. 55 Experimentally, by Auassisted mechanical exfoliation, Huang et al prepared more than 40 types of large-area single-crystalline monolayers, among which is GeS 2 in P 4m2 symmetry with a square lattice, but its properties have not been studied so far. 56 The above exciting ndings, especially the successful synthesis of the square conguration of the GeS 2 monolayer, prompt important questions: Would the other 2D TMDs adopt a square structure?…”
Section: Introductionmentioning
confidence: 99%
“…54 Qiao et al found that the SeN 2 monolayer is the only stable 2D crystal among 11 V–VI binary nanosheets with a square lattice. 55 Experimentally, by Au-assisted mechanical exfoliation, Huang et al prepared more than 40 types of large-area single-crystalline monolayers, among which is GeS 2 in P 4̄ m 2 symmetry with a square lattice, but its properties have not been studied so far. 56…”
Section: Introductionmentioning
confidence: 99%
“…[17] Additionally, to change the electron behaviors, the homologous structures S-XY 2 (X = S, Se, Te; Y = N, P, As, Te) are studied. [18] Also, some new structures have been studied recently. [19] It is commonly built van der Waals heterostructures or Janus structures to achieve charge interactions between layers.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Thus far, the experimentally obtained and theoretically proposed 2D materials mainly consist of hexagons, trigons and even pentagons, such as the hexagon-composed planar BN, 7 buckled silicene, germanene and stanene, 8 puckered phosphorene, 9,10 transition metal silicides, 11 trigonbased boronphene 12,13 and aluminene, 14 pentagonal graphene, 15 silicene, 16 B 2 C, 17 CN 2 , 18 AlN 2 , 19 B x N y , 20 and transition metal sulfides. 21 Besides, 2D square lattice structure materials, such as BiF trilayers, 22 Au and Pt monolayers and multilayers, 23 V-VI binary sheets, 24,25 and chalcogenides, 26 have also been theoretically proposed or experimentally synthesized; however, the stability of the squared Au and Pt sheets is yet to be examined. Moreover, many 2D materials with rule-breaking chemical bonding have been designed computationally based on the corresponding cluster models.…”
Section: Introductionmentioning
confidence: 99%